Sustainable wheat subspecies mixtures production by evaluating morphological traits and stability analysis of different varieties in different environments in Jordan - Amal Al Khatib; Nawal Al Hajaj; Yahya Bani Khalaf; Shihnaz Bsharat; Yansi Khasawneh; Mahmoud Al Hwayan; Ahamed Albatainah; Awad Al-Ka'abnh; Abdel Razzaq Al Tawaha; Maisaa Haddadin; Arun Karnwal (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Climate change and water scarcity present significant challenges to food security in arid and semi-arid regions, such as Jordan. Grains—particularly wheat—are essential for nutrition and national food security. This study addresses sustainable wheat production strategies under semi-arid conditions, focusing on the utilization of morphological characteristics through targeted breeding programs. Assessing genetic diversity is a critical prerequisite for evaluating population adaptation to novel environmental conditions. This study aimed to evaluate the morphological traits and yield stability of seven certified wheat (Triticum aestivum L.) varieties—ACSAD65, Ammoun, Cham1, Dair Alla6, Hourani, Mixture, and Um Qais—across three contrasting environments at Maru, Mushager, and Rabbah. These sites represent diverse agro-ecological zones within the semi-arid landscape of Jordan. The experiment was conducted using a randomized complete block design (RCBD) in a 3×7 factorial split-plot arrangement, where the three locations served as main plots and the wheat varieties as subplots. Results indicated that both location and growing season significantly affected yield and its components. The variety Um Qais exhibited the highest grain yield, while the mixture showed poor performance. Among the locations, Maru demonstrated superior performance in terms of biological yield, grain yield, straw yield, and harvest index, followed by Mushager and Rabbah. According to GGE biplot analysis, Um Qais emerged as the ideal genotype for grain yield, achieving the highest mean performance across all locations. These findings offer valuable insights for policymakers, agricultural researchers, and farmers by identifying high-yielding and stable wheat varieties that are adapted to local semi-arid environments.